2020
DOI: 10.1016/j.drugpo.2020.102832
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 - Enacting a ‘new normal’ for people who use drugs

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 15 publications
0
55
0
3
Order By: Relevance
“…Pandemics expose weaknesses in societies and bring to the fore a country’s ability to respond and protect its most vulnerable people [ 22 ]. Measures to mitigate the effects of COVID-19 have had serious social and economic impacts; although they have affected everyone, the impact is largest among marginalised and vulnerable populations [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pandemics expose weaknesses in societies and bring to the fore a country’s ability to respond and protect its most vulnerable people [ 22 ]. Measures to mitigate the effects of COVID-19 have had serious social and economic impacts; although they have affected everyone, the impact is largest among marginalised and vulnerable populations [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Service closures and disruptions have been reported in the United States, western and eastern Europe, sub-Saharan Africa, and Latin America and the Caribbean [ 22 , 25 – 28 ]. Our study found that all of the 13 participating harm reduction centres reported having had to modify or adapt their services.…”
Section: Discussionmentioning
confidence: 99%
“…Pandemics expose weaknesses in societies and bring to the fore a country's ability to respond and protect its most vulnerable people (22) responded) actually increased their operating hours during this period. Although Spain was one of the most heavily affected countries in the European Union, its network of harm reduction centres showed resilience by adapting policy changes and innovative strategies to deliver essential services to PWUD.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, if hospitals and clinics reach their capacity, disadvantaged populations such as PWID may experience even greater barriers to medical care for COVID-19. 15 Self-quarantine, physical distancing and other public health measures, the economic repercussions of the epidemic, and mental distress have disrupted access to syringe services programs, access to pharmacotherapies including medication for opioid use disorder (MOUD), and other support needed by people with opioid use disorder (OUD), 16 potentially putting this already disproportionately affected population at higher risk for HIV infection and drug overdose mortality. Likewise, disruptions in social services such as housing, food, and social counselling could complicate risk behaviour management and medical care provision for all PLHIV.…”
Section: Introductionmentioning
confidence: 99%